Design and synthesis of fluconazole/bile acid conjugate using click reaction - Pore, Vandana S.; Aher, Nilkanth G.; Kumar, Manish; Shukla, Praveen K. (Tetrahedron, 2006)
Novel fluconazole/bile acid conjugates were designed and their regioselective synthesis was achieved in very high yield via Cu(I) catalyzed intermolecular 1,3-dipolar cycloaddition. These new molecules showed good antifungal activity against Candida species. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Click chemistry; fluconazole/bile acid conjugate

Design, synthesis, and micellar properties of bile acid dimers and oligomers linked with a 1,2,3-triazole ring - Aher, Nilkanth G.; Pore, Vandana S.; Patil, Sachin P. (Tetrahedron, 2007)
1,3-Dipolar cycloaddition of propargyl esters of bile acids to azide group attached at different positions of bile acids gave dimers, trimer, and tetramer linked with 1,2,3-triazole. These dimeric and oligomeric structures were able to solubilize hydrophilic dye-cresol red, in nonpolar solvent. (c) 2007 Elsevier Ltd. All rights reserved.

Design and synthesis of bile acid-based amino sterols as antimicrobial agents - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Shukla, Praveen K.; Gonnade, Rajesh G. (Bioorganic & Medicinal Chemistry Letters, 2009)
New bile acid-based amino sterols were synthesized in good yields from C-3 beta-oxiranes as key intermediates. These derivatives were evaluated for their in vitro antimicrobial properties against human pathogens. These compounds showed better antibacterial activity as compared to antifungal activity. Compounds 21 and 22 showed comparable antibacterial activity to gentamicin against Staphylococcus aureus with IC(50) values of 5.14 and 4.46 mu g/mL. This is the first report for the synthesis of C-3 beta-oxiranes on the steroids having A/B cis ring junction and these oxiranes have been used for the synthesis of amino sterols 17, 18, 21, and 22. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amino sterols; Antibacterial agent; bile acid; Oxirane

Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Design and synthesis of new fluconazole analogues - Pore, Vandana S.; Agalave, Sandip G.; Singh, Pratiksha; Shukla, Praveen K.; Kumar, Vikash; Siddiqi, Mohammad I. (Organic & Biomolecular Chemistry, 2015)
We have synthesized new fluconazole analogues containing two different 1,2,3-triazole units in the side chain. The synthesis of new amide analogues using a variety of acids is also described. All the compounds showed very good antifungal activity. A hemolysis study of the most active compounds 6e and 13j showed that both compounds did not cause any hemolysis at the dilutions tested. These compounds did not exhibit any toxicity to L929 cells at MIC and lower concentrations. In the docking study, the overall binding mode of 6e and 13j appeared to be reasonable and provided a good insight into the structural basis of inhibition of Candida albicans Cyp51 by these compounds.